Determinación del material particulado pm2,5 y pm10 en el terminal terrestre de latacunga, provincia de Cotopaxi, periodo 2022. - Arevalo Bustillos, Luis Alexander (2022)
Air pollution is a worldwide problem caused by urban development, especially the growth of the automobile fleet and the consumption of low-quality fossil fuels such as diesel. In this research project, PM2,5 and PM10 particulate matter was determined in the Latacunga Land Terminal in the province of Cotopaxi, based on the characterization and diagnosis of the study area, through direct observation and use of bibliographic research, mainly from the land use plan of Latacunga, with the field visit, 6 sampling points were established, using E-BAM equipment to monitor particulate matter samples were taken every 10 minutes during 24 hours according to the equipment´s protocol, during the 12 days of July 2022. The methodology applied in the study was descriptive, analytical and field. The results of the average concentration of particulate matter in the 24 hours of PM2,5 were: point one 20µg/m3; point two 25µg/m3; point three 25µg/m3; point four 21µg/m3; point five 18µg/m3 and point six 21µg/m3, in the same way for particulate matter PM10 the following concentrations were obtained: point one 32µg/m3; point two 48µg/m3; point three 46µg/m3; point four 38µg/m3; point five 25µg/m3 and point six 42µg/m3, averages that do not exceed the maximum permissible limits established in the Regulations of the Ministerial Agreement 097-A Reform of the Unified Text of Secondary Legislation of the Ministry of the Environment (TULSMA ) Book VI Annex 4, where it specifies that, for PM2,5 the maximum permissible limit is 50µg/m3 and for PM10 the maximum permissible limit is 100µg/m3. The Latacunga Land Terminal has adequate infrastructure for its operation; however, it does not have a policy for follow-up, monitoring, and control of air pollution levels.